ChemInform Abstract: Surface and Interface Issues in Spinel LiNi0.5Mn1.5O4: Insights into a Potential Cathode Material for High Energy Density Lithium Ion Batteries. Issue 31 (14th July 2016) - Ma, Jun; Hu, Pu; Cui, Guanglei; Chen, Liquan
Abstract: Review: 227 refs.